PENGEMBANGAN KEMASAN DENGAN MENGGUNAKAN APLIKASI CANVA PADA UMKM KOPI 919 - Rahmat, Rahmat; Anastasia, Anastasia (ADMIT: Jurnal Administrasi Terapan, 2023)
The business world will always be faced with change, this is caused by many factors such as high competitiveness between companies and the high willingness of the public to change products so that they can be more practical to use. A company must be able to keep up with the times. , one way is by doing packaging development. UMKM Coffee 919 is a business located in Buludatu Housing Block B No.5. The packaging used by UMKM 919 is still very old-fashioned and seems outdated, so researchers will develop the packaging which includes 5 important aspects, namely the form of packaging, packaging materials, colors, fonts and brands. The purpose of this study was to determine the process of product development stages in Kopi 919 and also to create trending coffee packaging using the Canva application. This research was conducted for approximately four months, from April 2022 to August 2022 and went through 3 stages of research procedures, namely the creation of packaging ideas, filtering ideas and developing packaging. This study uses the type of data in the form of qualitative data. Data collection techniques in this study were carried out by observation (observation), interviews (interviews) and documentation. The results showed that standing pouch made of aluminum foil is suitable packaging for ground coffee and is liked by the public. In addition, storage period, logo/brand, net weight and composition are information that the public needs and the suitable colors for ground coffee products are brown and black.